Analisis nilai tambah pada rantai pasok produk kopi arabika dengan metode Hayami (studi kasus di kabupaten Aceh Tengah) - Dian Hasni; Yusriana Yusriana; Auliaddin Auliaddin (AGROINTEK, 2022)
Gayo coffee is a well-known name for arabica coffee planted in Gayo Highland (GH). In GH, coffee production has a significant role in life prosperity. Previous reports mentioned the wholesaler mainly influences coffee trades, and most farmers tend to have minor shares among the other supply chain actors. But the information related to the value of the shares within the chain is not well reported. This study aims to identify the shares of added value within the supply chain actors of Gayo coffee for the produced output based on the Hayami method. This research was conducted in Kebayakan and Bebesen. Two sub-districts in the GH area. These two sub-districts were selected for sampling because they have representation for all supply chain actors and others requirements. Data were collected by in-depth interviews based on a designed questionnaire towards the identified supply chain actors: independent/cooperative farmers, middlemen, cooperative, processing farmers, and wholesalers. The obtained results identified five supply networks available in GH that started from red cherries to the green bean. As first-tier suppliers, cooperative farmers who sold their products in green beans to cooperatives have added values up to 22,41% higher than independent farmers who rarely sold their green beans to the wholesaler. Independent farmers tend to sell their harvest directly to middlemen, as they only share added value of up to 6,25 % for selling red cherries and 10% for wet parchment coffee. Moreover, middlemen, cooperatives, processing farmers, and wholesalers act as a second-tier suppliers. Amongst those actors, processing farmers have the highest added value (43,53%) than others since they produce specialty coffee as a premium product. Cooperative and wholesalers received similar input from farmers, but wholesalers received slightly higher added value (22,53%) than cooperative (22,67%). Meanwhile, middlemen received higher added value by buying red cherries than wet parchment coffee from farmers.